Legal Protection Against the Use of Brand Names for Geographical Indications on Trusmi Cirebon Batik - Saefullah, Faiz; Kharisma, Icah; Riana Sari, Usri; Hidayat, Dudung; Ismayana (Ann Publisher, 2024)
The importance of conducting this research is because there is an allegation of violation of the law against the object of Geographical Indication registered as a brand name by an entrepreneur using the name